A Theoretical Study on Isolated Compounds from the Leaves Extract of Guiera Senegalensis as Aluminium Corrosion Inhibitor - Ayuba, A. M.; Abubakar, M. (Journal of Science and Technology, 2021)
The present work describes using computational methods the corrosion inhibition of aluminium using three selected chemical constituents (5-methyldihydroflavasperone, 5-methylflavasperone and methoxylated naphthyl butanone) reportedly obtained from the leaves extract of Guirea senegalensis. Quantum chemical calculations including EHOMO, ELUMO, energy gap (Î”E), electronegativity (Ï‡), global hardness (Î·) and fraction of electrons transfer from the inhibitor molecule to the aluminium surface (Î”N) were calculated. The local reactive sites through Fukui indices which explain the effect of structural features of these components in relation to electrophilic and nucleophilic point of attack were evaluated. The similarities in quantum chemical parameters for the compounds obtained revealed that the adsorption strengths of the molecules will be mostly determined by molecular size rather than electronic structure parameters. Fukui indices showed that the point of interaction of inhibitor molecule with the Al(1 1 0) surface were through aromatic carbon atom rich in pi-electrons and oxygen atom of the alkanone functional group in the inhibitor molecules. Molecular dynamics simulations describing the adsorption behavior of the inhibitor molecule on Al(1 1 0) surface through Forcite quench molecular dynamics were carried out. The compounds were found to all obey the mechanism of physical adsorption because of their relatively low adsorption energies.